Integrated Carnivore‐Ungulate Management: A Case Study in West‐Central Montana. Issue 1 (21st October 2020) - Proffitt, Kelly M.; Garrott, Robert; Gude, Justin A.; Hebblewhite, Mark; Jimenez, Benjamin; Paterson, J. Terrill; Rotella, Jay
ABSTRACT: Understanding the effectiveness of harvest regulations to manipulate population abundances is a priority for wildlife managers, and reliable methods are needed to monitor populations. This is particularly true in controversial situations such as integrated carnivore‐ungulate management. We used an observational before‐after‐control‐treatment approach to evaluate a case study in west‐central Montana, USA, that applied conservative ungulate harvest together with liberalized carnivore harvest to achieve short‐term decreases in carnivore abundance and increases in ungulate recruitment. Our study areas included the Bitterroot treatment area and the Clark Fork control area, where mountain lion populations ( Felis concolor ) were managed for a 30% reduction and for stability, respectively. The goals of the mountain lion harvest were to provide a short‐term reduction of mountain lion predation on elk ( Cervus canadensis ) calves and an increase in elk recruitment, elk population growth rate, and ultimately elk abundance. We estimated mountain lion population abundance in the Bitterroot treatment and Clark Fork control areas before and 4 years after implementation of the 2012 harvest treatment. We developed a multi‐strata spatial capture‐recapture model that integrated recapture and telemetry data to evaluate mountain lion population responses to harvest changes. Mountain lion abundance declined with increasing harvest in the Bitterroot treatment area from 161 (90% credible interval [CrI] = 104, 233) to 115 (CrI = 69, 173). The proportion of males changed from 0.50 (CrI = 0.33, 0.67) to 0.28 (CrI = 0.17, 0.40), which translated into a decline in the abundance of males, and similar abundances of females (before: males = 80 [CrI = 52, 116], females = 81 [CrI = 52, 117]; after: males = 33 [CrI = 20, 49], females = 82 [CrI = 49, 124]). In the Clark Fork control area, an area twice as large as the Bitterroot treatment area, we found no evidence of changes in overall abundance or proportion of males in the population. The proportion of males changed from 0.42 (CrI = 0.26, 0.58) to 0.39 (CrI = 0.25, 0.54), which translated into similar abundances of males and females (before: males = 24 [CrI = 16, 36], females = 33 [CrI = 21, 39]; after: males = 28 [CrI = 18, 41], females = 44 [CrI = 29, 64]). To evaluate if elk recruitment and population growth rate increased following treatment, we developed an integrated elk population model. We compared recruitment and population growth rate during the 5 years prior to and 5 years following implementation of the mountain lion harvest treatment for 2 elk populations within the Bitterroot treatment area and 2 elk populations within the Clark Fork control area. We found strong evidence that temporal trends differed between the 2 areas. In the Bitterroot treatment area, per capita elk recruitment was stable around an estimated median value of 0.23 (CrI = 0.17, 0.36) in the pre‐treatment period (2007–2011), increased immediately after treatment (2013) to 0.42 (CrI = 0.29, 0.56), and then declined to 0.21 (CrI = 0.11, 0.32) in 2017. In contrast, per capita elk recruitment estimates in the Clark Fork control area had similar median values during the pre‐ (2007–2011: 0.30, CrI = 0.2, 0.35) and post‐treatment periods (2013–2017: 0.31, CrI = 0.26, 0.36). These changes in recruitment corresponded to similar changes in elk population growth rate, although population growth rates were also subject to variation due to changing elk harvest. In the Bitterroot treatment area, population growth rates in the pre‐treatment period were stable to slightly declining, with an estimated median value of 0.92 (CrI = 0.88, 1.07) in the pre‐treatment period (2007–2011). Population growth rate during the post‐treatment period increased immediately after treatment (2012: 1.17, CrI = 1.14, 1.20) prior to declining to 1.06 (CrI = 1.04, 1.09) in 2016. In contrast, the median population growth rates were roughly equal in the Clark Fork control area during the pre‐treatment period (1.01, CrI = 0.86, 1.09) from 2007 to 2011 and post‐treatment period (1.00, CrI = 0.83, 1.15) from 2013 to 2017. Together, these results indicate that the harvest treatment achieved a moderate (i.e., 29%) reduction in mountain lion population abundance within the treatment area that corresponded with short‐term increases in elk recruitment and population growth. Elk population demographic responses suggest that the harvest treatment effect was strongest immediately after the mountain lion harvest treatment was implemented and lessened over time as the harvest treatment was reduced. This suggests that the short‐term harvest treatment resulted in short‐term demographic responses in elk populations, and more sustained harvest treatments would be necessary to achieve longer‐term elk population demographic responses. We recommend that wildlife managers seeking to balance carnivore and ungulate population objectives design rigorous carnivore and ungulate population monitoring programs to assess the effects of harvest management programs. Assessing and understanding effects of carnivore harvest management programs will help to set realistic expectations regarding the effects of management programs on carnivore and ungulate populations and allow managers to better design programs to meet desired carnivore and ungulate population objectives. RÉSUMÉ: Comprendre l'efficacité des règlements de récolte à contrôler l'abondance des populations est une priorité pour les gestionnaires de la faune, et des méthodes fiables sont nécessaires pour suivre l'état des populations. Cela est particulièrement vrai face à des situations controversées telles que la gestion intégrée des carnivores et des cervidés. Nous avons utilisé une approche observationnelle avant‐après‐témoin‐traitement dans le cadre d'une étude de cas prenant place dans le centre‐ouest du Montana, aux États‐Unis. L'étude impliquait une récolte de cervidés conservatrice et une récolte de carnivores plus permissive afin de réduire l'abondance des carnivores à court terme et d'augmenter le recrutement de cervidés. Nos aires d'étude comprenaient la zone expérimentale de la Bitterroot où la gestion visait à réduire les populations de couguars ( Felis concolor ) de 30%, ainsi que la zone témoin de Clark Fork où l'objectif était de maintenir des populations stables. La récolte de couguars visait la réduction à court terme de la prédation sur les faons de wapitis ( Cervus canadensis ), tout en augmentant le recrutement de wapitis, de même que le taux de croissance et l'abondance de leur population. Nous avons estimé l'abondance des couguars dans la zone de traitement de la Bitterroot et dans la zone témoin de Clark Fork avant la mise en œuvre du traitement de récolte en 2012, puis 4 ans après. Nous avons développé un modèle spatial de capture‐marquage‐recapture pour population stratifée qui intégrait des données de recapture et de télémétrie afin d'évaluer comment la population de couguars réagit aux variations du taux de récolte. L'abondance de couguars a diminué avec l'augmentation de la récolte dans la zone de traitement de la Bitterroot, passant de 161 (intervalle de crédibilité à 90% [ICr] = 104, 233) à 115 (ICr = 69, 173). La proportion de mâles est alors passée de 0, 50 (ICr = 0, 33, 0, 67) à 0, 28 (ICr = 0, 17, 0, 40), ce qui reflète la diminution de l'abondance des mâles et le maintien de l'abondance des femelles (avant: mâles = 80 [ICr = 52, 116], femelles = 81 [ICr = 52, 117]; après: mâles = 33 [ICr = 20, 49], femelles = 82 [ICr = 49, 124]). Dans la zone témoin de Clark Fork, une zone deux fois plus grande que la zone de traitement de la Bitterroot, nous n'avons détecté aucun changement dans l'abondance des mâles ou dans leur proportion au sein de la population. La proportion de mâles est passée de 0, 42 (ICr = 0, 26, 0, 58) à 0, 39 (ICr = 0, 25, 0, 54), se traduisant par une abondance similaire entre les mâles et les femelles (avant: mâles = 24 [ICr = 16, 36], femelles = 33 [ICr = 21, 39]; après: mâles = 28 [ICr = 18, 41], femelles = 44 [ICr = 29, 64]). Pour évaluer si le recrutement de wapitis et le taux de croissance de leur population ont augmenté suite au traitement, nous avons développé un modèle intégré des populations de wapitis. Nous avons comparé le taux de recrutement et de croissance de 4 populations de wapitis au cours des 5 années qui ont précédé et des 5 qui ont suivi le début de la récolte de couguars. Deux populations de wapitis se situaient dans la zone de traitement de la Bitterroot et 2 dans la zone témoin de Clark Fork. Nos résultats suggèrent fortement que les variations temporelles des populations différaient entre les 2 aires d'étude. Dans la zone de traitement de la Bitterroot, le recrutement des wapitis par individu était stable autour d'une valeur médiane de 0, 23 (ICr = 0, 17, 0, 36) durant la période de prétraitement (2007–2011), il a augmenté suite au traitement pour atteindre un niveau intermédiaire de 0, 42 (ICr = 0, 29, 0, 56) en 2013, puis il a diminué à 0, 21 (ICr = 0, 11, 0, 32) en 2017. En revanche, le recrutement des wapitis par individu avait des valeurs médianes similaires durant les périodes pré‐ (2007–2011: 0, 30, ICr = 0, 2, 0, 35) et de post‐traitement (2013–2017: 0, 31, ICr = 0, 26, 0, 36) dans la zone témoin de Clark Fork. Les variations du recrutement étaient liées à des changements similaires dans le taux de croissance des populations de wapitis, bien que le taux de croissance des populations ait également varié suite aux variations de récolte de wapitis. Dans la zone de traitement de la Bitterroot, les taux de croissance des populations étaient stables ou légèrement en baisse durant la période de prétraitement (2007–2011), avec une valeur médiane de 0, 92 (ICr = 0, 88, 1, 07). Le taux de croissance de la population a augmenté immédiatement après le traitement (2012: 1, 17, ICr = 1, 14, 1, 20), avant de diminuer à 1, 06 (ICr = 1, 04, 1, 09) en 2016. En revanche, le taux de croissance médian des populations de la zone témoin de Clark Fork est demeuré semblable entre la période prétraitement (1, 01, ICr = 0, 86, 1, 09) de 2007 à 2011 et celle post‐traitement (1, 00, ICr = 0, 83, 1, 15) de 2013 à 2017. Globalement ces résultats indiquent que le traitement de récolte a permis une réduction modérée (c.‐à‐d. 29%) de l'abondance des couguars dans la zone expérimentale, de même qu'une augmentation à court terme à la fois du recrutement et de la taille de la population de wapitis. Les changements démographiques de la population de wapitis suggèrent que l'effet du traitement de récolte a été maximal immédiatement après le début du traitement de récolte de couguars, puis a graduellement diminué suivant le réduction du taux de récolte. Ce résultat suggère que le traitement de récolte a eu une influence à court terme sur la démographie des populations de wapitis et, par conséquent, qu'un traitement de récolte plus soutenu serait nécessaire pour espérer un impact à plus long terme. Nous recommandons aux gestionnaires de la faune qui visent à gérer à la fois les populations de carnivores et de cervidés, de concevoir des programmes de surveillance permettant une évaluation rigoureuse des effets de la récolte sur ces populations. L'évaluation et la compréhension de l'effet des programmes de gestion de la récolte des carnivores aideront à établir des attentes réalistes quant aux effets de ces programmes sur les populations de carnivores et de cervidés, tout en permettant aux gestionnaires de concevoir des programmes permettant de mieux rencontrer les objectifs de gestion pour toutes ces populations.